PERKAWINAN SESUKU (BAGITO) MASYARAKAT MELAYU PETALANGAN DI KECAMATAN BANDAR PETALANGAN KABUPATEN PELALAWAN - Wahyu Masytah Yanti; Ashaluddin Jalil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The purpose of this research is to find out why sesuku and bagito marriages occur in the malay community petalangan, to find out whether there has been a shift custom og marriage to the malay community petalangan, and to find out how mamak ninik’s role is about sesuku and bagito marriages occur. Petalangan Malay suku located in the area Pelalawan Regency, the Petalangan suku adheres to the system the Matrilineal kinship. In Malay tradition of Petalangan, there are two marriages which must not be carried out, namely sesuku and bagito marriages. In this study using the theory of change social, with the number of key informan ang subjectas is as many as 6 people consisting of the Pebatin Bunut, Ninik Mamak And People who do sesuku and bagito mariage. The results of this study indicate that it occurred ethnic and sesuku marriage to the malay community Petalangan consists of several factors, namely influence outside, religion that dose not forbid, premarital pregnancy, sanctions which is not clumsy. This shift in sesuku and bagito marriage actually did not experience a very far shift but this shift was also influenced by technology develompments. Ninik mamak’s role in knowing the sesuku and bagito marriages have to socialize more about the community’s environments so that they know what are the rules contadined in the tradition of Malay Petalangan.  Keywords: Change, Sesuku Marriage and Bagito, Petalangan Malay.